2020
DOI: 10.1055/s-0039-3400264
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Intelligence in the Evaluation of Knee Pathology

Abstract: Artificial intelligence (AI) holds the potential to revolutionize the field of radiology by increasing the efficiency and accuracy of both interpretive and noninterpretive tasks. We have only just begun to explore AI applications in the diagnostic evaluation of knee pathology. Experimental algorithms have already been developed that can assess the severity of knee osteoarthritis from radiographs, detect and classify cartilage lesions, meniscal tears, and ligament tears on magnetic resonance imaging, provide au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Deep learning (DL) models have been proposed in medical imaging over recent years for an increasing number of tasks and with improving performances, fueled by strong collaborative efforts between radiologists and data scientists. detection models (usually focused on anterior cruciate ligament (ACL), meniscal or cartilage lesions) from MRI imaging have been proposed in the literature [5]. Bien et al [6] used aggregated 2D convolutional neural networks (CNN) to detect both general abnormalities and specific diagnoses (ACL and meniscal tears) from knee MRI examinations and published their dataset, MRNet.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning (DL) models have been proposed in medical imaging over recent years for an increasing number of tasks and with improving performances, fueled by strong collaborative efforts between radiologists and data scientists. detection models (usually focused on anterior cruciate ligament (ACL), meniscal or cartilage lesions) from MRI imaging have been proposed in the literature [5]. Bien et al [6] used aggregated 2D convolutional neural networks (CNN) to detect both general abnormalities and specific diagnoses (ACL and meniscal tears) from knee MRI examinations and published their dataset, MRNet.…”
Section: Introductionmentioning
confidence: 99%
“…The final result proposed an effective algorithm for the detection of PHF, and Chung further noted that the AI was able to improve the Neer classification, which brought profound significance for clinical PHF diagnosis and treatment [23] . Besides fracture detection, AI technology has also played an inspiring role in the diagnosis of other orthopedic diseases, such as scoliosis, arthritis, bone tumors, and meniscus and ligament injuries [24][25][26] . Taken together, these previous studies have confirmed the validity of AI-aided methods for clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The gap of the existing reviews [ 8 , 10 , 13 , 24 , 28 , 41 – 45 ] is that none of the reviews highlighted 3D CNN as well as its importance in OA studies. In addition, most of the review papers focused on knee anatomical segmentation approaches instead of classification approaches in OA diagnosis.…”
Section: Gap Of Knowledgementioning
confidence: 99%
“…Recent studies have adapted artificial intelligence (AI) and have increasingly recognized the role of deep learning in the medical field, including computer-aided knee OA diagnosis [ 10 , 11 ] which is aimed to reduce uncertainties in diagnosis due to human error [ 12 ]. The significant motivation in the development of AI in OA research is the availability of huge repositories of clinical and imaging data such as through Osteoarthritis Initiative (OAI) [ 13 ]. There are different types of architecture of deep learning such as convolutional neural network (CNN), recurrent neural network (RNN), recursive neural network, and unsupervised pretrained network (UPN) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%